Impacts of different salinities on growth performance, stress response, and feeding activity of shortfin Eel, Anguilla bicolor - Stefanie Maria Ayu Raganata; Shigeharu Senoo; Ching Fui Fui @ Faihana Ching Abdullah (The Malaysian Society of Applied Biology, 2024)
Due to the declining wild fishery stock of Shortfin eel (Anguilla bicolor), eel aquaculture has become increasingly important in Southeast Asian countries. Consequently, there is a rising urgency to cultivate A. bicolor as an export commodity due to its high demand and value. However, little is known about the optimum culture conditions to enhance the optimal growth performance of A. bicolor in captivity. Four different salinities (0, 10, 20, 30 ppt) were tested on A. bicolor for 28 days and its growth performance, stress level, and feeding activity were investigated. Findings revealed A. bicolor was able to survive in all salinities without any mortality recorded. Meanwhile, A. bicolor gained significantly higher body weight at 10 ppt (4.33±0.87) compared to those in 0, 20, and 30 ppt despite being insignificant different in the final total length. A. bicolor reared in 10 ppt also attained relatively higher feed intake and low feed conversion ratio indicating its excellent feeding utilization. No significant differences were also found in the stress level of A. bicolor in all salinities indicating its tolerance and adaptation in all salinities. The present study concludes 10 ppt as suggested salinity to further enhance the growth of A. bicolor as it promotes excellent feeding performance, low stress levels, and overall optimal growth.